Penanaman Sikap Sosial Melalui pembelajaran IPS Pada Siswa Kelas V Di MI Nurul Huda Blerong - Wahidah, Ifana Nafiatussania; Shofa Nailil Husna (AL-IHTIRAFIAH: JURNAL ILMIAH PENDIDIKAN GURU MADRASAH IBTIDAIYAH, 2024)
The aim of this research is to find out how to instill social attitudes through social studies learning and the obstacles faced when instilling social attitudes along with the efforts made to overcome the obstacles that occur in class V MI Nurul Huda Blerong students. This type of research is qualitative research using qualitative descriptive methods located at MI Nurul Huda Blerong. The samples in this study were fifth grade students and homeroom teachers. The data collection instruments in this research consisted of interviews, observations and documentation which were then analyzed. The results of this research are the methods used by teachers to instill social attitudes in students through social studies learning in class V MI Nurul Huda Blerong, namely instilling the values ​​of social attitudes in students with social studies learning strategies and so on, the obstacles faced by teachers in instilling social attitudes in students namely limited study time at school, family conditions and others, and efforts to overcome the obstacles faced by teachers in instilling social attitudes in students, namely working together with students' parents, consulting with other teachers, holding discussions with students' parents. Keywords: Cultivation, Constraints, Attitude, Social.